Are We There Yet? An Emerging Research Agenda for College Students with Intellectual and Developmental Disabilities. Issue 2 (March 2021) - Brady, Michael P.
There is a distinct need for a research agenda that drives research, practice, and policy for college students with intellectual and developmental disabilities. This paper provides a brief summary of the rapid growth of college programs in the absence of any organized research agenda. A research framework and agenda is proposed, and a brief summary of each of the papers in the special issue is provided.